2016
DOI: 10.5812/ijhrba.34928
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Validity and Reliability of Internet Infidelity Questionnaire among Internet Users in Iran

Abstract: Background: Today the internet has become a part of our everyday life; communicating online has made it easy for people to begin and develop interpersonal relationships. Certain problems, however, appear to result directly from relationships online. One of these problems which has been prevalent among couples and families is extramarital internet relationships or internet infidelity. Study of this phenomenon in Iranian users' needs a tool for evaluation. Objectives: This study has been done to validate the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Berhubungan seks secara virtual, mengirim email yang immoral dan tidak menyenangkan, menonton pornografi bersama, menunjukkan gambar diri melalui kamera daring, mendis-kusikan kehidupan seks, mengirim foto telanjang), seba-nyak 12 item. Alat ukur pertama kali dikembangkan oleh Docan-Morgan & Docan (2007) dan telah diuji kembali oleh Nooripour (2016).…”
Section: Metode Penelitianunclassified
“…Berhubungan seks secara virtual, mengirim email yang immoral dan tidak menyenangkan, menonton pornografi bersama, menunjukkan gambar diri melalui kamera daring, mendis-kusikan kehidupan seks, mengirim foto telanjang), seba-nyak 12 item. Alat ukur pertama kali dikembangkan oleh Docan-Morgan & Docan (2007) dan telah diuji kembali oleh Nooripour (2016).…”
Section: Metode Penelitianunclassified
“…Millions of such users may be married, seriously dating, or cohabiting individuals, and they may use the Internet to meet strangers, flirt, and many times engage in highly sexualized conversations (Mileham, 2007). The large number of couples involved in extra-dyadic Internet relationships and online infidelity is a growing problem (Gerson, 2011;Nooripour et al, 2016). The difficulty of such relationships has led couples to seek help from counselors and therapists.…”
Section: Introductionmentioning
confidence: 99%
“…Instruments for the investigation of the Internet infidelity phenomenon have been limited. Literature review suggests that among the tools used, the Internet Infidelity Scale of Docan-Morgan and Docan ( 2007) has high reliability and validity as an investigative research instrument and was found to be a valid and reliable measure in many foreign studies (Kallay, 2019 (Nooripour et al, 2016). Furthermore, Suliakaite (2009) developed an Online Behavior Questionnaire that was primarily based on the Internet Infidelity Scale constructed by Docan-Morgan and Docan (2007), with the scope of exploring Lithuanians' attitudes and perceptions toward Internet infidelity and investigating whether interpersonal and intrapersonal factors were associated with the attitudes toward online affairs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation